Determination of the scaling characteristics of time-dependent optical properties of microalgae using electromagnetic scattering. (22nd January 2021) - Ma, C Y
Abstract: The time-dependent optical properties of microalgae are crucial for light transfer in photobioreactor (PBR) designs. In this study, the time-dependent optical properties were derived using electromagnetic scattering theory informed by the experimentally measured optical properties of Chlorella protothecoides . The temporal scaling functions (TSFs) of nearly wavelength-independent absorption and scattering cross-sections were demonstrated using electromagnetic scattering theory, leading to the first concrete expression of the TSF. The TSF establishes the relationship between the time-dependent absorption/scattering cross-sections in the stationary and growth phases of microalgal development. The concrete expression of the TSF provides a new means of calculating the time-dependent optical properties of microalgae using electromagnetic scattering theory. The TSF of microalgae has great potential in remote sensing and PBR applications.